Design of an Enhanced Public Health Surveillance System for Hepatitis C Virus Elimination in King County, Washington. (January 2020) - Baer, Atar; Fagalde, Meaghan S.; Drake, Curtis D.; Sohlberg, Elisabeth H.; Barash, Elizabeth; Glick, Sara; Millman, Alexander J.; Duchin, Jeffrey S.
Introduction: With the goal of eliminating hepatitis C virus (HCV) as a public health problem in Washington State, Public Health–Seattle & King County (PHSKC) designed a Hepatitis C Virus Test and Cure (HCV-TAC) data system to integrate surveillance, clinical, and laboratory data into a comprehensive database. The intent of the system was to promote identification, treatment, and cure of HCV-infected persons (ie, HCV care cascade) using a population health approach. Materials and Methods: The data system automatically integrated case reports received via telephone and fax from health care providers and laboratories, hepatitis test results reported via electronic laboratory reporting, and data on laboratory and clinic visits reported by 6 regional health care systems. PHSKC examined patient-level laboratory test results and established HCV case classification using Council of State and Territorial Epidemiologists criteria, classifying patients as confirmed if they had detectable HCV RNA. Results: The data enabled PHSKC to report the number of patients at various stages along the HCV care cascade. Of 7747 HCV RNA-positive patients seen by a partner site, 5377 (69%) were assessed for severity of liver fibrosis, 3932 (51%) were treated, and 2592 (33%) were cured. Practice Implications: Data supported local public heath surveillance and HCV program activities. The data system could serve as a foundation for monitoring future HCV prevention and control programs.